Agreement of Transvaginal Ultrasound (TVS) and Per Operative Findings in Detecting Retained Products of Conception - M. Zafar Rafique, Moazma Ejaz, Maimoona Gulshan, Mehwish Tahir, Maham Abid, Binyamin Butt (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the diagnostic accuracy of TVS and Per-operative findings in diagnosing retained products of conceptions (RPOCs) Methods: A total of 161 suspected cases of RPOCs, visited the Radiology department, Shalamar Hospital, Lahore from 01-01-2021 to 31-12-2021were done ultrasound using high-frequency probe for TVS.. Results: Out of 161 patients, 97 were found to have RPOCs on TVS. The mean age was 29.54±6.10 and the mean gestational age was17.02±12.99. In 97(60.2%) cases having RPOCs, 46(63.9%) cases were with H/o abortion, 39(79.6%) with miscarriages, 12 cases (30%) with C-section. This study shows a significant association between TVS finding and per-operative findings i.e. 97(60.2%) cases have RPOCs detected by ultrasound and also detected by per-operative finding of mild and moderate amount of RPOCs. Conclusion: TVS is the initial modality for detecting RPOCs. USG is a noninvasive technique and can be done on portable USG machine. Key words: Retained products of conception, TVS, USG